STUDI PENGARUH PEMAHAMAN PRODUK PADA PENGAMBILAN KEPUTUSAN MENGGUNAKAN TELKOM FLEXI (Studi Kasus: PT TELKOM Kandatel Surabaya Barat) - Winarni Kurniasari; Haryono Haryono; Vita Ratnasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
In order to choose the right TELKOM Flexi product, prospecting customers need a guide for a better understanding of the products. Therefore, it is important for the company to measure how far the understanding level of the prospecting customers relates to the decision making in product selection. The decision level may give significant influence to marketing strategy of TELKOM Flexi. In analysis of confirmatory, indicators which were used to form unobserved variables comprised: Product Category Knowledge (PCK), Perceived Ease ofUse (PEU), Perceived Usefulness (PU) and Decision Confidence (DC). These indicators were significant, as shown by probability value of statistic smaller than 10%. Each indicator can be assumed to form unidimensionalities to each unobserved variables. Result of examination pursuant to criterion Goodness of Fit Indices of by using Structural Equation Modelling. Results of questioner's data processing showed that PCK had a direct influence of significance to PEU, PEU have influence of significant to PU, and PU had an influence of significance to DC. As a conclusion, the customers decided to buy Flexi because of the Perceived Ease of Use and Perceived Usefulness. Therefore, PT TELKOM Kandatel of West Surabaya should base the marketing strateu on these two factors.